Evaluation of tensile strength and hardness of weld beads by Smaw and Mig-Mag processes - Villarreal Albitres, William Fernando (2021)
Welding constitutes a type of permanent joint in the assembly process in the secondary manufacturing industry such as construction for the manufacture of automobiles, aircraft, bridges, tanks, ships, pipes, among others. The objective of this research was to compare the mechanical tensile strength and hardness of welded specimens. The mechanical traction was to evaluate the resistance to breakage of the weld seams by the MIG/MAG process versus the SMAW welding process, on ASTM 36 base material. The hardness was to determine the plastic deformation of the area affected by heat during the fusion process. For this purpose, the universal testing machine was used to determine the stress-strain relationship of each process; while a hardness tester was used for hardness. In this experiment, 12 welded specimens and two non-welded control specimens were used to determine the quantitative deviation of breakage and hardness, with respect to the specimens subjected to experimental tests. To determine the supremacy in mechanical properties, the t-value statistical tool was used. The results indicated that the stress-strain relationship of the specimens showed the same stages and characteristics of elastic and plastic deformation until failure. Likewise, it was found that the MIG/MAG procedure presents higher tensile strength and hardness values than SMAW, so our zero hypothesis that stated that the SMAW process had better mechanical properties had to be rejected. It is concluded that the MIG/MAG welding process has superior mechanical properties than the SMAW process.